Enhancing regional convergence in the European Union - Pina, Álvaro (OECD Publishing, 2021)
Progress in regional convergence in the EU has been uneven over the last two decades. While Central and Eastern Europe has been catching up, Southern Europe has often lost ground, especially after the global financial crisis. Furthermore, within most countries, gaps between large cities and rural areas have widened. Some challenges to convergence have stemmed from worldwide factors - such as globalisation, digitalisation, global warming, and, more recently, COVID19 - but others are European-specific, like incomplete financial integration, less effective fiscal governance and subpar innovation performance. This paper proposes policy action to reduce regional divergence by helping regions upgrade their productive specialisation. Building on new approaches to regional and industrial policies, Europe needs to exploit the full potential of cross-country cooperation in innovation and of urban agglomeration economies. Competition and trade policies need to ensure a level playing field to enhance the benefits of open and competitive markets while responding to new challenges, such as digitalisation or foreign subsidies. Finally, Cohesion Policy and the Common Agricultural Policy, the two largest EU budget instruments, need to become more effective at promoting productive upgrading
Keywords: Economics